PA 20-1-2450 Descriptive epidemiology of rape and sexual assault data, kaduna state, nigeria, 2013–2015. (November 2018) - Lawal, Lukman Ademola; Akpan, Ubong; Oladimeji, Abisola M; Balogun, Muhammad Shakir; Nguku, Patrick
Abstract : Globally, 7% of women had experience non-partner sexual violence (SV) in their lifetime. Demonstrated consequences of SV include unintended pregnancy, sexually transmitted infection and HIV, substance use and abuse and injury. According to the Nigeria 2013 National Demographic and Health Survey, 4.6% of Kaduna state women aged 15–49 have ever experienced SV, the highest in the Northwest zone of Nigeria. We carried out a study to describe the epidemiologic characteristics of reported SV cases in Kaduna state. We carried out a secondary data analysis of all SV records between 2013 and 2015 obtained from the Kaduna state police command family unit. We defined categories of SV according to the Penal code law of federation of Nigeria. We extracted information on sociodemographic characteristics of survivors and perpetrators, survivor/perpetrators relationship and medical outcome. A total of 90 cases of sexual violence reported from 9 of the 23 Local Government Areas within the period. A yearly increase in number of reported cases (24 (26.7%), 32 (35.6%), and 34 (37.8%) was observed from 2013 to 2015 respectively. Eighty-two (91.1%) of the survivors were female. The median ages (range) of survivors and perpetrators were 10 years (3–20 years) and 26 years (10–80 years) respectively. The SVs reported were indecent assault 5 (5.6%), unnatural offence 8 (8.9%), attempted rape 20 (22.2%) and Rape 57 (63.3%). Sixty-five (72%) of perpetrators were known to survivors. In 61 (67.8%) cases, a neighbor was the perpetrator of violence. Eighty-seven (96.7%) of cases received medical care and 56 (62.9%) survivors sustained injuries and laceration. In Kaduna State, reported sexual violence occur more frequently among children and youths. There is a need to enhance sexual violence awareness among parent and caregivers. We recommended that the state should carry out mass campaign on sexual violence awareness at community level.